Morphological and morphometric study of elongation of the styloid process with calcification of the stylohyoid ligament in a human skull: a case report - Pacífico, Fernando Augusto (2023)
Elongation of the styloid process can compress nearby structures, causing a set of symptoms that characterize Eagle Syndrome. There is a lack of studies, especially in the Brazilian population, on the morphological and morphometric aspects of the lengthening of the styloid process. Therefore, the present study reports a case of elongation of the styloid process with calcification of the stylohyoid ligament bilaterally, in which the length of these structures on both sides exceeded twice that necessary to meet the anatomical criterion for the existence of the syndrome, as well asdetailed the morphological and morphometric aspects and the clinical implications of the aforementioned structures.detailed the morphological and morphometric aspects and the clinical implications of the aforementioned structures.